The Effect of Competence and Engagement on Employee Performance: The Mediation Role of Organizational Citizenship Behavior - Artati, Noor Endah; Suyati, Sri (Faculty of Economics and Business UNTAG Semarang, 2024)
The study aimed to analyze the influence of employee competence and engagement on employee performance mediated role by organizational citizenship behavior (OCB). The sample size used was 93 respondents of employees of Kedungwuni I and II Health Centers, Pekalongan Regency, Central Java, Indonesia. The sample was taken using proportional random sampling, and the data was analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The results show that competence and employee engagement have a positive effect on OCB. Further findings revealed that competence, employee engagement, and OCB influence toward employee performance. Based on the mediation test, the study concludes that OCB can mediate role in employee performance. This study contributes theoretically by elucidating the pathways through which competence and engagement influence performance and emphasizing OCB as a valuable mediator in this relationship. This framework can guide future research and practical applications for fostering high performance in the workplace.